Spatiotemporal parameters of the operated and non-operated knees before and after unilateral total knee arthroplasty - Bilek, Furkan; Deniz, Gulnihal; Esmez, Omer; Belhan, Oktay (Elsevier Ireland Ltd, 2022)
Background: Knee osteoarthritis is a common condition in various orthopedic clinics and hospitals. The aim of this study was to investigate the effects of unilateral total knee arthroplasty (TKA) application on short and longterm spatiotemporal gait parameters, maximum plantar pressure (MPP), and functional status in patients with knee osteoarthritis. Research question: What is the change process in spatiotemporal parameters without any intervention before and after TKA surgery? Methods: This study is a prospective and cross-sectional study. Participants were assessed preoperatively at the 1st week (Pre1W), postoperative 1st month (Post1M) and 6th month (Post6M). Spatiotemporal parameters and MMP were assessed using the Win Track platform (Medicapteurs Technology, France) and functional states were assessed using the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and the Lequesne Index. Results: Significant improvements were found in the WOMAC and Lequesne Index values in the Post1M and Post6M periods compared to the preoperative period. However, the improvement in WOMAC and Lequesne Index scores in the Post6M period was significant compared to the scores in the Post1M period (p < 0.01). Spatiotemporal parameters deteriorated in the Post1M period, while improvements were observed in the Post6M period. We observed that patients had worse gait parameters in the near postoperative period than before surgery. It was the period with the greatest improvements in long-term outcomes. Significance: In the light of our study results, we think that early gait disturbances in patients who underwent direct TKA may be caused by physiological processes. Therefore, we believe that there is no need for any intervention for gait disorders that occur in the early postoperative period.
Keywords: Gait; Loading; Osteoarthritis; Spatiotemporal parameters; Total knee arthroplasty